Pengaruh Tayangan TVRI Sumsel Terhadap Minat Masyarakat Dalam Konten Budaya Lokal - Muhammad Fadliansyah; Sumaina Duku; Ahmad Harun Yahya (CV. ITTC INDONESIA, 2024)
Television Republik Indonesia (TVRI) broadcasts aspects of public life and arts and culture in Palembang. Local cultural shows are a program that is very suitable for introducing local culture in the area by providing the latest information packaged in an interesting way so that people have a high level of interest to pay greater attention to maintaining their own culture so that it is not lost due to lack of caring. This research aims to find out TVRI South Sumatra's broadcasts about people's interests and to find out TVRI South Sumatra's shows about local cultural content. This research uses a quantitative type of research with a survey approach, namely looking for questionnaire results and observing descriptions of the influence of TVRI broadcasts on people's interest in local cultural content. This research variable consists of two variables, namely the independent variable (influence of TVRI Sumsel broadcasts) and the dependent variable (public interest in local cultural content). Data collection techniques were carried out using questionnaires, observation methods and documentation. The results of this study show that from the 50 respondents sampled, it can be seen that the influence of TVRI Sumsel broadcasts (Variable Meanwhile, the significance value = 0.006 with a significance of 5% or 0.05, meaning there is a significant influence between the two variables. The R Square value is 0.637 (64%), meaning it can be said that the two variables between variables X and Y have a strong relationship. Then, if you look at the t-test results of t = 9.172 > 2.407 and the significance is 0.000, it can be concluded that there is an influence of South Sumatra TVRI broadcasts on public interest in local cultural content. It is hoped that this research will serve as an evaluation and suggestion for television managers to pay more attention to balanced information so that viewers are more interested in watching shows on TVRI Sumsel. Apart from that, the public is also expected to be more selective in choosing shows to prioritize news content, they have to be smarter and catchier in taking in the messages broadcast on a television program.